Mobile diagnostics: next-generation technologies for in vitro diagnostics. Issue 7 (14th March 2018) - Shin, Joonchul; Chakravarty, Sudesna; Choi, Wooseok; Lee, Kyungyeon; Han, Dongsik; Hwang, Hyundoo; Choi, Jaekyu; Jung, Hyo-Il
Abstract : The emergence of a wide range of applications of smartphones along with advances in 'liquid biopsy' has significantly propelled medical research particularly in the field of in vitro diagnostics (IVD). Abstract : The emergence of a wide range of applications of smartphones along with advances in 'liquid biopsy' has significantly propelled medical research particularly in the field of in vitro diagnostics (IVD). Herein, we have presented a detailed analysis of IVD, its associated critical concerns and probable solutions. It also demonstrates the transition in terms of analytes from minimally invasive (blood) to non-invasive (urine, saliva and sweat) and depicts how the different features of a smartphone can be integrated for specific diagnostic purposes. This review basically highlights recent advances in the applications of smartphone-based biosensors in IVD taking into account the following factors: accuracy and portability; quantitative and qualitative analysis; and centralization and decentralization tests. Furthermore, the critical concerns and future direction of diagnostics based on smartphones are also discussed.